Hak Privasi vs Kepentingan Negara dalam Pengawasan Siber: Menemukan Keseimbangan Konstitusional di Era Digital Panopticon - Gilang Rizki Aji Putra (BULETIN ADALAH, 2022)
The tension between citizens’ privacy rights and state cyber surveillance has become a major constitutional issue in the digital era. This article analyzes the constitutional limits of state surveillance and explores a balance between security interests and democracy. Using normative legal research with conceptual, statutory, and comparative approaches, the study finds that Indonesia’s cyber surveillance framework lacks proportionality, judicial oversight, and accountability. Regulations under the ITE Law and Intelligence Law grant broad discretion without adequate due process safeguards. The article recommends stronger judicial supervision, limiting executive discretion, and establishing a special supervisory court chamber. Keywords: Privacy Rights, Cyber Surveillance, State Interests, Proportionality, Due Process.